The sedimentology and formation of the Gígjökull and Kvíárjökull latero-frontal moraines, Iceland - Minney Sigurðardóttir 1986- (2014)
Large latero-frontal moraines are prominent landforms in valley glacier landsystems and are key features in glacier and palaeoclimatic reconstruction. However, compared to other types of moraines, their sediemtology and mode of formation is still poorly understood. A comprehensive sedimentological study of the large latero-frontal moraines of Gígjökull and Kvíárjökull in South Iceland is presented. Dominating the proglacial landscape, the moraines are 1-3 km long, 300-700 m wide and 70-150 m high above their valley floors. The proximal slopes are 20-75° and usually steepest closest to the ice front, while their distal slopes vary between 10 and 30°. The sedimentology was studied in 35 sections excavated in the upper most parts of the moraines; 21 at Gígjökull and 14 at Kvíárjökull. The sections vary from 0.7-2.5 m in height. Two main sedimentary facies were identified; 1) diamict, varying from massive to stratified, and 2) sorted sediments including fines, sand and gravel. The properties of the diamict indicate that they were formed as supraglacial accumulations of ice-contact debris and are interpreted as subaerial debris flow tills. Low to moderate RA and C40 indices and weak clast fabric (S1 0.3-0.6) strongly suggest a previous active subglacial transport of the flow till sediments. The sorted sediments are interpreted as glaciofluvial deposits forming kame terraces superimposed on the proximal slopes of the moraines. The proposed model claims that these large latero-frontal moraines are formed by dumping of mainly subglacial debris from a supraglacial position and superimposed of glaciofluvial deposition during series of advances and re-advances. Stórir jökulgarðar eru áberandi landform í jökulsvorfnu landslagi og eru með helstu landformun sem notast er við í rannsóknum á hegðun og útbreiðslu jökla og loftslagsbreytingum fyrri tíma. Stórir jökulgarðar, sem myndast meðfram og framan við skriðjökla, oft nefndir jaðargarðar, eru hinsvegar lítt rannsakaðir og myndun þeirra því illa þekkt. Hér eru kynntar ...